Macrocyclic lactone based tri-model therapy to treat humpsore in cattle under humid tropical island ecosystem - PERUMAL, P; DE, A K; BHATTACHARYA, D; CHAKURKAR, E B (The Indian Journal of Animal Sciences, 2023)
Humpsore is a chronic parasitic dermatitis in bovine species; induces severe economic losses to the dairy farmers. Various therapeutic methodologies were tried to treat humpsore in the past; however, they were partially effective against humpsore. Therefore, the present study was designed to assess the effect of tri-model therapy [macrocyclic lactone; Ivermectin, a piperazine derivative; diethylcarbamazine citrate (DECC) and an herbal ointment; Himax™] on treatment of humpsore in Andaman and Nicobar islands. Thirty‐six cattle (n=36 affected) were selected and divided into Gr 1: control (infected without treatment; n=18) and Gr 2: treatment group (infected with treatment; ivermectin, DECC and Himax, n=18) in South Andaman district. In Gr 2, treatment to the ailing animals was given for 45 days. Physiological profiles, hematological profiles, biochemical profiles [total protein, TP; albumin, AL; globulin, GL; creatinine, CR; glucose, GLU; total cholesterol, CHO and urea, URE], liver functional enzymes [aspartate aminotransferase, AST; alanine aminotransferase, ALT and alkaline phosphatase, ALP], mineral profiles, oxidative stress profiles [total antioxidant capacity, TAC; superoxide dismutase, SOD; catalase, CAT and malondialdehyde, MDA] and cortisol were estimated on day 30 of post treatment. Lesion was significantly reduced in day 15 of post‐treatment and completely healed on day 45 of post‐treatment in Gr 2. Physiological profiles, liver functional enzymes, urea, total white blood cell count, differential cell counts, MDA and cortisol were reduced significantly and blood profiles, biochemical profiles, mineral profiles and antioxidant profiles were increased significantly in tri-model therapy treated animals. Therefore, it can be concluded that tri‐model therapy is suitable to treat humpsore in dairy animals.